The ‘red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic - Gardner, Joel; Gibbs, Jason (European Journal of Taxonomy, 2020)
Sweat bees in the subgenus Lasioglossum (Dialictus) are one of the most diverse and abundant bee taxa, and a critically important component of bee biodiversity. Yet, the most basic taxonomic knowledge of these bees is lacking in many regions. As a step towards a better understanding of the L. (Dialictus) of the western Nearctic region, a revision of the ‘red-tailed’ L. (Dialictus) species was completed. Thirty-six species were revised, 20 of which are described as new, and two names are treated as junior subjective synonyms. Descriptions, figures, distribution maps, floral hosts, and keys to species for females and males are provided. The following 20 species are described as new: Lasioglossum (Dialictus) arenisaltans sp. nov., L. (D.) argammon sp. nov., L. (D.) austerum sp. nov., L. (D.) cactorum sp. nov., L. (D.) cembrilacus sp. nov., L. (D.) clastipedion sp. nov., L. (D.) clavicorne sp. nov., L. (D.) decorum sp. nov., L. (D.) festinum sp. nov., L. (D.) imbriumbrae sp. nov., L. (D.) julipile sp. nov., L. (D.) lilianae sp. nov., L. (D.) meteorum sp. nov., L. (D.) miltolepoides sp. nov., L. (D.) minckleyi sp. nov., L. (D.) perditum sp. nov., L. (D.) rufornatum sp. nov., L. (D. ) spivakae sp. nov., L. (D.) tessellatosum sp. nov., and L. (D.) torrens sp. nov. Previously unknown males of L. (D.) clematisellum (Cockerell, 1904), L. (D.) droegei Gibbs, 2009, L. (D.) kunzei (Cockerell, 1898), and L. (D.) pallidellum (Ellis, 1914) are described and figured for the first time. Lasioglossum (Dialictus) clarissimum (Ellis, 1914) (= Halictus clarissimus Ellis, 1914) and L. (D.) perexiguum (Sandhouse, 1924) (= Halictus (Chloralictus) perexiguus Sandhouse, 1924) are new subjective junior synonyms of L. mesillense (Cockerell, 1898) (= Halictus nymphalis var. mesillensis Cockerell, 1898). A lectotype specimen is newly designated for L. mesillense, for which the location of the type material has not previously been known. The following five new records for Mexico are reported: L. clematisellum, L. droegei, L. eophilus (Ellis, 1914), L. kunzei, and L. pallidellum.